1998
DOI: 10.1006/viro.1998.9383
|View full text |Cite
|
Sign up to set email alerts
|

Human Serum Attenuates the Activity of Protease Inhibitors toward Wild-Type and Mutant Human Immunodeficiency Virus

Abstract: The potency of therapeutic regimens containing human immunodeficiency virus (HIV) protease inhibitors is related to the ability to maintain concentrations of drug in the plasma of patients that are sufficient for blocking viral replication. The estimation of concentrations required for in vivo activity using in vitro assays is complicated by the fact that extensive binding of many protease inhibitors to serum proteins attenuates their antiviral potency. To provide insight into the relative in vivo potency of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
116
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 25 publications
5
116
3
Order By: Relevance
“…In contrast, nelfinavir and saquinavir inhibited the glucose-stimulated insulin secretion at a 20-times lower concentration. This is again in contrast to the inhibitory effects on viral replication, where the free indinavir concentration only needed to be two or three times higher than nelfinavir and saquinavir to attain similar effects (IC 50 0·041, 0·025 and 0·014 µM for indinavir, nelfinavir and saquinavir respectively; Molla et al 1998). Since indinavir has lower serum protein binding and thus results in a higher free indinavir concentration, it was effective at even lower concentrations than nelfinavir and saquinavir if 50% human serum was present (IC 50 0·09, 0·92 and 0·37 µM for indinavir, nelfinavir and saquinavir, respectively; Molla et al 1998).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In contrast, nelfinavir and saquinavir inhibited the glucose-stimulated insulin secretion at a 20-times lower concentration. This is again in contrast to the inhibitory effects on viral replication, where the free indinavir concentration only needed to be two or three times higher than nelfinavir and saquinavir to attain similar effects (IC 50 0·041, 0·025 and 0·014 µM for indinavir, nelfinavir and saquinavir respectively; Molla et al 1998). Since indinavir has lower serum protein binding and thus results in a higher free indinavir concentration, it was effective at even lower concentrations than nelfinavir and saquinavir if 50% human serum was present (IC 50 0·09, 0·92 and 0·37 µM for indinavir, nelfinavir and saquinavir, respectively; Molla et al 1998).…”
Section: Discussionmentioning
confidence: 89%
“…This is again in contrast to the inhibitory effects on viral replication, where the free indinavir concentration only needed to be two or three times higher than nelfinavir and saquinavir to attain similar effects (IC 50 0·041, 0·025 and 0·014 µM for indinavir, nelfinavir and saquinavir respectively; Molla et al 1998). Since indinavir has lower serum protein binding and thus results in a higher free indinavir concentration, it was effective at even lower concentrations than nelfinavir and saquinavir if 50% human serum was present (IC 50 0·09, 0·92 and 0·37 µM for indinavir, nelfinavir and saquinavir, respectively; Molla et al 1998). These data for the effects on virus replication and our results, based on a long-term incubation period, therefore suggest that, compared with the effect on virus replication, indinavir causes less impairment of insulin secretion than nelfinavir and saquinavir.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…It has been demonstrated that drugs including certain antiviral compounds show markedly reduced activity in vivo or in cellular models because of their natural tendency to bind serum proteins (Molla et al, 1998). To evaluate this possibility, the inhibitory effect of the antiviral candidates should be measured in cells cultured in media containing increasing concentrations of human serum (Huang et al, 2008).…”
Section: Hcv Targeting By New Chemical Entitiesmentioning
confidence: 99%